Fetal skeletal dysplasia cohort of a single tertiary referral center in Istanbul, Turkey. Issue 2 (17th November 2022) - Kalayci, Tugba; Altunoglu, Umut; Çorbacioglu Esmer, Aytul; Avcı, Şahin; Sarac Sivrikoz, Tugba; Karaman, Birsen; Kalelioğlu, İbrahim; Has, Recep; Uyguner, Zehra Oya; Yüksel, Atıl; Başaran, Seher; Kayserili, Hülya
Abstract: We report on 314 fetal cases from 297 unrelated families with skeletal dysplasia evaluated in the postmortem period from 2000 to 2017 at a single clinical genetics center in İstanbul, Turkey. The definite diagnostic yield was 40% during the prenatal period, while it reached 74.5% when combined with postmortem clinical and radiological evaluation. Molecular analyses were performed in 25.5% ( n : 76) of families, and 21 novel variants were identified. Classification according to International Skeletal Dysplasia Society‐2019 revision revealed limb hypoplasia‐reduction defects group (39) as the leading one, 24.5%, then followed by FGFR3 chondrodysplasias, osteogenesis imperfecta, and decreased mineralization and polydactyly‐syndactyly‐triphalangism groups 13.6, 11.1, and 8.9%, respectively. The inheritance pattern was autosomal recessive in 54% and autosomal dominant in 42.6% of index cases. The overall consanguinity rate of the cohort was 33%. The high prevalence of ultrarare diseases along with two or more unrelated autosomal recessive entities running in the same family was noteworthy. This study highlights the pivotal role of postmortem evaluation by an experienced clinical geneticist to achieve a high diagnostic yield in fetal skeletal dysplasia cohorts. The cohort is not only a representation of the spectrum of skeletal dysplasias in a population with a high consanguinity rate but also provides an ideal research group to work on to identify the unknowns of early fetal life.